Monitoring flux in signalling pathways through measurements of 4EBP1-mediated eIF4F complex assembly - Yuri Frosi; Rachael Usher; Dawn Thean Gek Lian; David P. Lane; Christopher J. Brown (BMC Biology, 2019)
Abstract Background The most commonly occurring cancer mutations, including oncogenes such as MYC, Ras and PIK3C, are found in signal transductions pathways feeding into the translational machinery. A broad range of translation initiation factors are also commonly found to be either amplified or mis-regulated in tumours, including eIF4E (elongation initiation factor 4E). eIF4E is a subunit of the eIF4F protein initiation complex and required for its recruitment. Here we measure the formation of the eIF4F complex through interactions of eIF4E and eIF4G subunits, and the effect of oncogenic signalling pathways on complex formation. Results We developed a protein fragment complementation (PCA) assay that can accurately measure the status of the eIF4E-eIF4G interaction in cells and quantify the signalling flux through the RAS/ERK and PI3K/AKT pathways regulating eIF4F assembly. Complex disruption induced by inhibition of either pathway was shown to be a function of the phosphorylation status of 4EBP1, a key mediator of eIF4F assembly that interacts directly with eIF4E, confirming 4EBP1’s ability to integrate multiple signals affecting cap-dependent translation. Maximal measured disruption of the eIF4F complex occurred under combined mTORC1 and mTORC2 inhibition, whilst combined inhibition of both RAS/ERK and PI3K/AKT pathways in parallel resulted in greater inhibition of eIF4F formation than individually. v-Myc-mediated resistance to dual mTORC/PI3K inhibition was also principally demonstrated to depend on the lack of competent 4EBP1 available in the cell to bind eIF4E. Conclusions We show that 4EBP1 is a critical regulator of the mitogen responsive RAS/ERK and PI3K/AKT pathways and a key transducer of resistance mechanisms that affect small molecule inhibition of these pathways, principally by attenuating their effects on cap-dependent translation. These findings highlight the importance of highly efficacious direct inhibitors of eIF4E and eIF4F assembly, which could potentially target a wide spectrum of tumours containing differing mutations that effect these pathways and which confer chemo-resistance.